Krzywda i jej zadośćuczynienie w prawie cywilnym. Analiza pojęć w świetle orzecznictwa sądów polskich - Klimkiewicz, Artur (Zeszyty Naukowe Katolickiego Uniwersytetu Lubelskiego Jana Pawła II, 2020)
In the current legal status, the basis for property claims may be, among others the fact so-called harm suffered. Art 448 Polish Civil Code prescribe that In the event of infringement of one’s personal interests the court may award to the person whose interests have been infringed an appropriate amount as monetary recompense for harm suffered (…). How to interpret the meaning of the term “harm suffered”. What is the relationship of this term to such terms as „ non-pecuniary damage” or „mental suffering”? These issues are currently the subject of scientific discussion and judicial decisions. The purpose of this article was therefore to report the existing views on the interpretation of the above-mentioned concepts and to lay out the grounds for seeking monetary compensation. The article also presents the circumstances that are of prime importance for mending the amount of compensation for harm suffered .